2020
DOI: 10.3389/fpubh.2020.00106
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Public Health Interventions: A Neglected Area in Health Technology Assessment

Abstract: Introduction: Public health (PH) interventions are crucial for ensuring sustainable healthcare services. Nevertheless, they represent a neglected area in the field of health technology assessment (HTA) due to various methodological issues and their complex design that goes beyond clinical setting. The present study provides an environmental scan of HTA initiatives related to the assessment of PH technologies on a global level.Methods: We conducted a cross-sectional survey among 85 HTA-related European and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…We aimed to evaluate the transferability of PH intervention data from 52 international HTA professionals to ICHI and to describe our coder experiences with the ICHI classification. We generally found that ICHI provides a good coverage of PH interventions, despite the challenges we faced due to the lack of detailed reporting in the original survey ( 5 ). The broader character of system wide interventions, often involving a variety of institutions and stakeholders, may have presented a hurdle to the application of ICHI coding (including actions, targets and means).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We aimed to evaluate the transferability of PH intervention data from 52 international HTA professionals to ICHI and to describe our coder experiences with the ICHI classification. We generally found that ICHI provides a good coverage of PH interventions, despite the challenges we faced due to the lack of detailed reporting in the original survey ( 5 ). The broader character of system wide interventions, often involving a variety of institutions and stakeholders, may have presented a hurdle to the application of ICHI coding (including actions, targets and means).…”
Section: Discussionmentioning
confidence: 99%
“…In total, 52 respondents from all continents answered the survey. The majority came from European countries (34%), followed by North American (26.9%) and South American countries (19.2%) ( 5 ). The obtained information was entered in a standard data collection extraction spread sheet (Microsoft Excel, version 2016) and categorized according to the ICHI.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…HTAs are most commonly undertaken to assess often narrowly defined decision problems for single classes of technologies including drugs, medical devices, and screening programs. Processes of care, public health interventions, and other complex interventions are less commonly assessed; however, the value of such analysis is recognized (2).…”
Section: Introductionmentioning
confidence: 99%